Upaya Meningkatkan Hasil Belajar PAI pada Materi Asmaul Husna dengan Menggunakan Metode Index Card Match di SDN 08 Seluma - Yeyen Mardanita; Kasmantoni Kasmantoni (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
This study is motivated by the existence of students who still have difficulty in memorizing the names of ALLAH in Asmaul husna, students are less actively involved in the learning process, and the low average score of students in mastering this asmaul husna material. This research is a class action research conducted in Class IV SDN Kecamatan Talo Kecil Seluma Regency, totaling 11 people, divided into 6 boys and 5 girls. Data collection techniques and tools in this study were tests, observations and discussions conducted in 2 cycles. The research findings are first, the application of the Index Card Match method where students look for pairs of Asmaul Husna names and their meanings, which then fill in the worksheet and present their findings to the front of the class. Second, the Index Card Match method can improve student learning outcomes in Asmaul Husna material.